The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2217/pgs-2019-0108
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Pediatric Anesthesia and Pain Management: Problem-Based Review

Abstract: Pharmacogenetics, the genetic influence on the interpersonal variability in drug response, has enabled tailored pharmacotherapy and emerging ‘personalized medicine.’ Although oncology spearheaded the clinical implementation of personalized medicine, other specialties are rapidly catching up. In anesthesia, classical examples of genetically mediated idiosyncratic reactions have been long known (e.g., malignant hyperthermia and prolonged apnea after succinylcholine). The last two decades have witnessed an expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 150 publications
(162 reference statements)
0
2
0
2
Order By: Relevance
“…Fatalities have been reported in infants breastfed by mothers taking codeine, in children following adenotonsillectomy and other surgeries, particularly in the presence of apnea and obesity [49]. A review of adverse effects in children taking codeine-containing products found cases of severe respiratory depression and death [50]. This has led to the development of guidelines and clinical practice guidelines for the use of codeine by the World Health Organization, the FDA, the European Medicines Agency (EMA), and Health Canada, as well as the Medicines and Healthcare products Regulatory Agency Great Britain [50].…”
Section: Data On the Pediatric Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatalities have been reported in infants breastfed by mothers taking codeine, in children following adenotonsillectomy and other surgeries, particularly in the presence of apnea and obesity [49]. A review of adverse effects in children taking codeine-containing products found cases of severe respiratory depression and death [50]. This has led to the development of guidelines and clinical practice guidelines for the use of codeine by the World Health Organization, the FDA, the European Medicines Agency (EMA), and Health Canada, as well as the Medicines and Healthcare products Regulatory Agency Great Britain [50].…”
Section: Data On the Pediatric Populationmentioning
confidence: 99%
“…A review of adverse effects in children taking codeine-containing products found cases of severe respiratory depression and death [50]. This has led to the development of guidelines and clinical practice guidelines for the use of codeine by the World Health Organization, the FDA, the European Medicines Agency (EMA), and Health Canada, as well as the Medicines and Healthcare products Regulatory Agency Great Britain [50]. Restrictions have been established for the use of codeine in children under 12 years of age after adenotonsillectomy procedures [51].…”
Section: Data On the Pediatric Populationmentioning
confidence: 99%
“…Agencja odradza także zastosowanie tych leków wśród kobiet karmiących piersią ze względu na możliwe szkody dla niemowląt. [8] Zastosowanie morfiny, najczęściej stosowanego leku z grupy agonistów μ-receptorów, uznawanie jest obecnie za złoty standard. [1] Farmakokinetyka morfiny u dzieci nie jest obecnie dokładnie przeanalizowana, dlatego też jej zastosowanie w populacji pediatrycznej powinno być dokładnie monitorowane przez doświadczony personel.…”
Section: Leczenie Farmakologiczneunclassified
“…Wykazano jego dużą skuteczność w zwalczaniu bólu u dzieci. [8] [10] W Polsce jego używanie jest popularne podczas występowania tzw. bóli przebijających u dzieci z procesem nowotworowym.…”
Section: Leczenie Farmakologiczneunclassified